Human xenoreactivity is reduced in mice bearing porcine antisense alpha(1,3) galactosyltransferase cDNA - Ma Ying-Hua; Zhou Xiao-Gang; Hu Jia-Hua; Fei Jian; Xia Guo-Hong; Guo Li-He (Acta Pharmacologica Sinica, 2016)
Aim: To explore the effect of antisense alpha(1,3) galactosyltransferase alpha(1,3) GT cDNA on production of Gal alpha(1,3) Gal (Gal epitope) xenoantigen in vivo. Methods: Transgenic mice bearing the porcine antisense alpha(1,3) GT cDNA (nt 1alpha-640) were generated by pronuclei microinjection method. The integration of transgene was identified by PCR and Southern-blot analysis. The expression of murine alpha(1,3) GT was characterized by RT-PCR. Morphology of the spleen was examined by histological technique. Gal epitope was detected by immunofluorescent analysis. Binding of human natural xenoantibodies (IgM and IgG) and complement (C3c) to cells from mice was determined by flow cytometric assay. Results: Transgenic mice bearing the porcine antisense alpha(1,3) GT cDNA were born healthy and developed normally. However, necrosis occurred in the spleen of some mice heterozygous for transgene. Cell surface Gal epitope in transgenic heterozygotes was evidently reduced. Substantially less (30 % - 60 %) xenoantibodies in human serum bound to cells from a variety of tissues of transgenic heterozygotes compared with wild-type controls. Consequentially, human complement activation on cells from these mice was reduced by 40 % - 50 %. Conclusion: Human xenoreactivity could be effectively reduced by inhibiting the expression of alpha(1,3) galactosyltransferase with an antisense gene.